(untitled) (Medical Forum Monthly, 2024)
Objective: Traumatic brain injury is one of the leading causes of morbidity, mortality and severe economic loss; especially in the patients who are in productive years of life. The objective of our study was to find out the etiological pattern and distribution of traumatic brain injury at Mirpur, Azad Kashmir. Study Design: Prospective study. Place and Duration of Study: This study was carried out at surgical wards at DHQ hospital, Mirpur from Nov 2012 to April 2013. Materials and Methods: In this study epidemiological and clinical data of all the patients with traumatic brain injury admitted in surgical wards at DHQ hospital, Mirpur were included. Results: A total of 309 patients with traumatic brain injury were admitted. The age range was between 3 years to 80 years. The mean age was 23.8 years. The most commonly affected age group was between 25-30 years (89.3%). Males were predominant (81.9%). Students involved constituted 44.7% of patients. Commonest mode of trauma was pedestrians hit by motorized vehicles (70 %) followed by physical assaults (15.9%). Majority of the patients (88.3 %) were from local district and 70.2 % reached the hospital within two hours of trauma. 46.6 % of the patients had a GCS of 13-15 on arrival. 3.9% had subdural hematoma while 1% of patients had skull fractures and intracerebral bleeds. Overall mortality was 5.8%. Conclusion: Road traffic accidents are the leading cause of traumatic brain injury affecting the young population at Mirpur and led to 5.9% mortality and 9.5 % total dependency in the affected population. Better traffic control system and awareness can reduce the incidence of traumatic brain injuries